The review of adaptive educational hypermedia system based on learning style - Bayasut, Bilal Luqman; Pramudya, Gede; Basiron, Halizah (2013)
Accommodating learning style in adaptive educational hypermedia system (AEHS) may lead to an increased effectiveness and efficiency of the learning processes as well as teacher and learner satisfaction. The premise is that a fact that learning in classroom is less efficient, when teachers will not be able to get insight of each of the student’s learning style hence, they wont be able to adapt their teaching strategies to match with the student’s learning style. In order to get insight of the student’s learning style in AEHS, the system must be able to recognize the learning style of the students. Current methods for recognizing learning styles are less efficient, where questionnaires or surveys were used to the students, which lead to tedium and disturbance at learning processes. By using proposed approaches which are multilayer feed forward artificial neural network (MLFF), fragment sorting, and adaptive annotation technique, this study will design and develop an AEHS.